Appearance and analysis of a reflecting coating damage - Schubert Martin; Elgeti Stefan; Hunger Katja; Grigore Eduard; Ruset Cristian; Neu Rudolf; Stober Jörg; Vorbrugg Stefan; Zammuto Irene (EPJ Web of Conferences)
Eight reflecting gratings are installed into the plasma facing wall of ASDEX Upgrade (AUG) in order to provide a controlled second pass through the plasma centre in 140 GHz heating scenarios with reduced single pass absorption. Four of these gratings are machined out of W1.4901 steel and coated with tungsten to increase the reflectivity. During plasma operation three of them worked very well, only one showed a strong correlation between the launcher On-time and an unusual increase in plasma radiation. After completion of the 2022 experimental campaign, this tile was carefully inspected. Traces of local melting were visible and the tile was examined with a scanning electron microscope to determine the surface material composition. The image of backscattered electrons revealed that tungsten is missing locally and along some of the ridges of the complex topology of this grating. Within these areas, the steel surface started to melt, which is in accordance with the assumption, that an intact tungsten coating indeed prevents the steel from melting. The damaged tile is currently being replaced and we have implemented two measures in order to prevent such damage on the new tile. The first measure is to consequently finish all machining steps before the coating procedure. This is because a mechanical damage of the coating before the installation could not be ruled out. The second measure is to control and minimize the surface roughness after machining and before the coating procedure. It turned out that the roughness was up to 3 microns in the past, which seems to be too high for the desired quality of this particular coating. We have tested and developed an electropolishing procedure to decrease the surface roughness to the order of 1 micron and keep the grating topology as precise as possible.